Pemberdayaan Masyarakat melalui Pengelolaan Keuangan Rumah Tangga - Annisa, Dea; Nurmala, Putri; Sigit, Akhmad (Jurnal PKM Manajemen Bisnis, 2024)
Household financial management is the process of achieving goals through structured and appropriate finances. Many households do not yet have planning and management to achieve their financial goals. Therefore, this activity aims to transfer knowledge and knowledge in managing the household finances of the Mothers of the Nurul Ikhsan Taklim Council, so that the Mothers can be independent in keeping simple household financial records. The method used is in the form of delivering material and how to use household financial applications. The activity showed that before the PKM, the mothers did not have enough knowledge about financial management and making simple financial records, but after carrying out the activity it was discovered that the mothers of the Nurul Ikhsan Taklim Council were able to know how to make simple household financial reports and knew the application. can help record digital-based finances. PKM activities indirectly play a positive role in increasing participants' knowledge and skills in making simple financial reports.